Identifying credit supply shocks with bank-firm data: Methods and applications - Hans Degryse; Olivier De Jonghe; Sanja Jakovljević; Klaas Mulier; Glenn Schepens (National Bank of Belgium, 2018)
Current empirical methods to identify and assess the impact of bank credit supply shocks rely strictly on multi-bank firms and ignore firms borrowing from only one bank. Yet, these single-bank firms are often the majority of firms in an economy and most prone to credit supply shocks. We propose and underpin an alternative demand control (using industry-location-size-time fixed effects) that allows identifying timevarying cross-sectional bank credit supply shocks using both single- and multi-bank firms. Using matched bank-firm credit data from Belgium, we show that firms borrowing from banks with negative credit supply shocks exhibit lower financial debt growth, asset growth, investments, and operating margin growth. Positive credit supply shocks are associated with bank risk-taking behaviour at the extensive margin. Importantly, to capture these effects it is crucial to include the single-bank firms when identifying the bank credit supply shocks.
Keywords: G21; G32; 330; credit supply identification; bank lending; corporate investment; bank risk-taking